Studi Awal Pengembangan Instrumen Pengukuran Keberlanjutan Perguruan Tinggi di Indonesia - Athalia, Nadia; Hariandja, Johanna Renny Octavia; Wibisono, Yogi Yusuf (Universitas Katolik Parahyangan, 2025)
As a way to achieve sustainable development, it is important to develop a tool for assessing sustainability of Indonesian universities. There is one tool created by an Indonesian university, which have been utilized by 1,183 universities worldwide. However, the participation of Indonesian universities in sustainability assessment using this tool is considered very low, only 3.12% or about 145 universities in Indonesia. This statistic calls for an effort to develop a new assessment tool that accommodates the context of Indonesian universities. The objective of this research is to develop a sustainability assessment tool that is effective, relevant with the context of Indonesian universities and includes a data input system that is simple to use. The research involves identifying relevant sustainability dimensions, determining indicator criteria suitable for Indonesian context, designing easy data input, and evaluating the validity and reliability of the tool. This study uses a literature review of 29 current measuring tools used globally, which revealed four primary areas (i.e. environment, economics, education, and social). According to this preliminary study, the typical measurement tool averagely has forty indicators. Moreover, it is observed that current tools have some unsuitable indicators to Indonesian context (i.e. infrastructure, environment, and information). This study has streamlined the tool to three primary areas (i.e. environment, social, and education) and 18 assessment indicators. As a follow up study, expert talks, pairwise comparison analysis, and the design and testing of the sustainability assessment tool will be carried out.